Pervasive Positive Selection on Virus Receptors Driven by Host-Virus Conflicts in Mammals - Wang, Wenqiang; Han, Guan-Zhu (Journal of virology, 2021)
Viral receptors are cellular proteins hijacked by viruses to help their infections. A complete picture on the evolution of viral receptors in mammals is still lacking. Viruses hijack cellular proteins, known as viral receptors, to initiate their infections. Viral receptors are subject to two conflicting directional forces, namely, negative selection to maintain their cellular function and positive selection resulted from the ever-changing host-virus arms race. Much remains unclear about how viral receptors evolved in mammals and whether viral receptors from different mammal groups experienced different strengths of natural selection. Here, we perform evolutionary analyses of 92 viral receptors in five major orders of mammals, including Carnivora, Cetartiodactyla, Chiroptera, Primates, and Rodentia. In all five mammal orders, signals of positive selection are detected for a high proportion of viral receptors (from 41% in Carnivora to 65% in Rodentia). Many positively selected residues overlap the host-virus interaction interface. Compared with control genes, we find viral receptors underwent elevated rates of adaptive evolution in all five mammal orders, suggesting that host-virus conflicts are the main driver of the adaptive evolution of viral receptors in mammals. Interestingly, the overall strength of natural selection acting on viral receptors driven by the host-virus arms race is largely homogenous and correlated among different mammal orders, with bats and rodents, zoonosis reservoirs of importance, being unexceptional. Taken together, our findings indicate host-virus conflicts have driven the elevated rate of adaptive evolution in viral receptors across mammals and might have important implications in zoonosis surveillance and prediction. IMPORTANCE Viral receptors are cellular proteins hijacked by viruses to help their infections. A complete picture on the evolution of viral receptors in mammals is still lacking. Here, we perform a comprehensive evolutionary analysis of the evolution of 92 viral receptors in five mammal orders, including Carnivora, Cetartiodactyla, Chiroptera, Primates, and Rodentia. We find that positive selection pervasively occurred during the evolution of viral receptors, and viral receptors exhibit an elevated rate of adaptive evolution compared to that of control genes in all five mammal orders, suggesting host-virus conflicts are a major driver of the adaptive evolution of viral receptors. Interestingly, the strength of positive selection acting on viral receptors is similar among the five mammal orders. Our study might have important implications in understanding the evolution of host-virus interaction.